A Study on Gen Z’s Preference for Bollywood Movies Vs. Web Series in Ahmedabad - Sanjit Mahota; Jignesh Vidani (MultiTech Publisher, 2024)
This study investigates Generation Z's preferences for Bollywood movies versus web series in Ahmedabad, with a focus on gender-based differences in media consumption behaviors. As digital platforms such as streaming services have gained popularity, understanding the evolving media consumption habits of younger audiences is essential. The research uses primary data and hypothesis testing to examine the relationships between gender and various media consumption factors, including the frequency of watching Bollywood movies, web series, genre preferences, and the choice of viewing platforms (theater versus streaming). The findings reveal that gender significantly influences the frequency of watching Bollywood movies and web series, with males showing a slightly higher tendency to watch Bollywood movies, while web series attract both genders more equally. Genre preferences in Bollywood movies did not show a significant gender-based difference, suggesting that content in this area is increasingly appealing to a broader audience. However, gender did impact genre preferences for web series, with males tending to prefer action and thriller genres, while females gravitated towards drama and romance genres. Additionally, a significant relationship was found between gender and platform preference, with males more likely to prefer watching content in theaters, while females favored streaming platforms. These insights have practical implications for content creators, marketers, and streaming platforms, highlighting the need to tailor content and promotional strategies to align with gender-specific preferences